Quantum-Behaved Lightning Search Algorithm to Improve Indirect Field-Oriented Fuzzy-PI Control for im Drive - Hannan M.A.; Ali J.A.; Mohamed A.; Amirulddin U.A.U.; Tan N.M.L.; Uddin M.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Fuzzy logic; Induction motors; Learning algorithms; Mean square error; Membership functions; Optimization; Particle swarm optimization (PSO); Rotors; Speed; Speed control; Stators; Torque; Transient analysis; Vector control (Electric machinery); Voltage control; Water craft; Backtracking search algorithms; Fuzzy membership function; Gravitational search algorithm (GSA); Indirect field oriented control; PI Controller; QLSA; Speed controller; Three phase induction motor; Controllers